1975
DOI: 10.1128/aem.29.1.54-58.1975
|View full text |Cite
|
Sign up to set email alerts
|

Biological Modification of Trichothecene Mycotoxins: Acetylation and Deacetylation of Deoxynivalenols by Fusarium spp

Abstract: Attempts were made to elucidate the acetyl transformation of novel trichothecene mycotoxins, 3a,7a,15-trihydroxy-12,13-epoxytrichothec-9-en-8-one (deoxynivalenol) and its derivatives, by trichothecene-producing strains of Fusarium nivale, F. roseum, and F. solani. In the peptone-supplemented Czapek-Dox medium, F. roseum converted 3a-acetoxy-7a,15-dihydroxy-12,13epoxytrichothec-9-en-8-one (3-acetyldeoxynivalenol) to deoxynivalenol. 3-Acetyldeoxynivalenol was also deacetylated by intact mycelia of the three stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…A similar trend was observed in DON-contaminated spikes, wherein the frequencies of 3-ADON were 16% (6 days), 19% (29 days), 3% (62 days) and 1% (107 days). Thus, the conversion of 4-ANIV and 3-ADON to the parent toxins was indicated in the spikes, supporting the author's previous hypothesis that the deacetylation in the field is induced by biological hydrolysis during the maturation of cereal grain, probably by host-plant enzymes 86) .…”
Section: Occurrence Of Mycotoxigenic Fusarium Species and Don/niv Onsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar trend was observed in DON-contaminated spikes, wherein the frequencies of 3-ADON were 16% (6 days), 19% (29 days), 3% (62 days) and 1% (107 days). Thus, the conversion of 4-ANIV and 3-ADON to the parent toxins was indicated in the spikes, supporting the author's previous hypothesis that the deacetylation in the field is induced by biological hydrolysis during the maturation of cereal grain, probably by host-plant enzymes 86) .…”
Section: Occurrence Of Mycotoxigenic Fusarium Species and Don/niv Onsupporting
confidence: 83%
“…The author first found the microbial acetylation at the C-3α position of DON with resting mycelia of F. nivale Fn2B (=F. kyushuense) 86) . The acetyl conjugation of T-2 toxin, HT-2 toxin and neosolaniol, each having a C-3α hydroxy group, was also studied by using mycelia of trichothecene-producing strains of F. graminearum, F. nivale (=F.…”
Section: Acetyl Conjugation Of Trichothecenes 97)mentioning
confidence: 99%
“…Growing mycelia of the fungus that had been grown on peptone-supplemented Czapek-Dox medium (pH 6.8) in a shaking flask at 20 C for 3 days were washed three times with 0.67 M phosphate buffer (pH 6.8). Deoxynivalenol (VII) and its derivatives were prepared as previously described (10,17,19). Fusarenon (II) and T-2 toxin (XIV) were isolated from peptone-supplemented Czapek-Dox media of F. nivale and F. solani, respectively, by the procedure described by Ueno et al (11,14).…”
Section: Methodsmentioning
confidence: 99%
“…thecenes by intact mycelia of F. nivale or F. solani was performed in sugar-free Czapek-Dox medium under the same conditions as previously described (19). Chemical transformation of trichothecenes was performed in methanolic ammonium hydroxide at 5 C for an appropriate period, and methanol was evaporated in vacuo.…”
Section: 'Iha3mentioning
confidence: 99%
“…Recently, we found that T-2 toxin is converted to HT-2 toxin (3,4-dihydroxy-15-acetoxy-8-isovaleroxy-12,13-epoxy-A9-trichothecene) in F. poae (NRRL 3287) liquid cultures (manuscript submitted for publication). The isolation of acetyl T-2 toxin from the same strain of F. poae, and the recent work by Yoshizawa and Morooka (10) showing that the 3-acetoxy group of 3a,7a,15-triacetoxy-12,13-epoxytrichothec-9ene-one is particularly susceptible to enzymatic hydrolysis by Fusarium solani, have led us to suspect that acetyl T-2 toxin is the immediate biogenetic precursor of T-2 toxin. If this is the case, any observed T-2 toxicosis associated with F. poae (= F. tricinctum) contamination of field samples may well be dependent upon the relative efficiency of C-3 deacetylation in acetyl T-2 toxin.…”
mentioning
confidence: 99%